2008
DOI: 10.1007/s11554-008-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time anomaly detection in hyperspectral images using multivariate normal mixture models and GPU processing

Abstract: Hyperspectral imaging, which records a detailed spectrum of light arriving in each pixel, has many potential uses in remote sensing as well as other application areas. Practical applications will typically require real-time processing of large data volumes recorded by a hyperspectral imager. This paper investigates the use of graphics processing units (GPU) for such real-time processing. In particular, the paper studies a hyperspectral anomaly detection algorithm based on normal mixture modelling of the backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Commodity graphics processing units (GPUs) are well known to satisfy heavy computing requirements. 7,8 GPUs are normally used to process graphics on personal computers and are relatively inexpensive. Such graphics cards can potentially boost processing speed due to the inherent parallelizability of hyperspectral data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Commodity graphics processing units (GPUs) are well known to satisfy heavy computing requirements. 7,8 GPUs are normally used to process graphics on personal computers and are relatively inexpensive. Such graphics cards can potentially boost processing speed due to the inherent parallelizability of hyperspectral data processing.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved using e.g. GPU processing, [8][9][10][11][12][13][14] multi-core, memory-optimized CPU processing or FPGA processing. 8 Such processing algorithms will contribute to an earlier diagnostic answer after image acquisition and reduce the total processing cost after the image has been fully obtained.…”
Section: -6mentioning
confidence: 99%
“…A GPU-based implementation of the RX algorithm, recently proposed by Winter et al, can also be found in Ref. 14 Another GPUbased implementation of a target detection algorithm for real-time anomaly detection in HSI has recently been proposed by Tarabalka et al 15 The proposed anomaly detection algorithm is based on a multivariate normal mixture model of the background.…”
Section: Target Detection Algorithmsmentioning
confidence: 99%